2022
DOI: 10.1101/2022.11.24.22282706
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accelerated absorption of regular insulin administered via a vascularizing permeable microchamber implanted subcutaneously in diabeticRattus norvegicus

Abstract: In Type 1 diabetes patients, even ultra-rapid acting insulins injected subcutaneously reach peak concentrations in 45 minutes or longer. The lag time between dosing and peak concentration, as well as intra- and inter-subject variability, render prandial glucose control and dose consistency difficult. We postulated that insulin absorption from subcutaneously implantable vascularizing microchambers would be significantly faster than conventional subcutaneous injection. Male athymic nude R. norvegicus rendered di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Indeed, enhancing the connection between insulin‐producing cells and host vasculature has been shown to help the delivered cells sense glucose, transport therapeutic paracrine/endocrine factors, and secrete insulin on demand 18 . In addition to increasing the survival of delivered cells, vascularizing the subcutaneous space enhances medication absorption; Steyn et al found that implantable, vascularizing microchambers rapidly increased exogenous insulin uptake compared to conventional subcutaneous injections 19 . As such, strategies to increase vascularization in the subcutaneous space have been pursued and are summarized in the subsequent paragraph.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, enhancing the connection between insulin‐producing cells and host vasculature has been shown to help the delivered cells sense glucose, transport therapeutic paracrine/endocrine factors, and secrete insulin on demand 18 . In addition to increasing the survival of delivered cells, vascularizing the subcutaneous space enhances medication absorption; Steyn et al found that implantable, vascularizing microchambers rapidly increased exogenous insulin uptake compared to conventional subcutaneous injections 19 . As such, strategies to increase vascularization in the subcutaneous space have been pursued and are summarized in the subsequent paragraph.…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition to increasing the survival of delivered cells, vascularizing the subcutaneous space enhances medication absorption; Steyn et al found that implantable, vascularizing microchambers rapidly increased exogenous insulin uptake compared to conventional subcutaneous injections. 19 As such, strategies to increase vascularization in the subcutaneous space have been pursued and are summarized in the subsequent paragraph. To prioritize clinical translation, any vascularization strategy must minimize technical, safety, and regulatory burdens.…”
mentioning
confidence: 99%